Phenotypic and Biochemical Characterization of Secreted Virulence Factors from Pseudomonas aeruginosa on Selective Agar Media - Shujon Hassan Jadaan, (American Journal of Biology and Natural Sciences, 2026)
Pseudomonas aeruginosa is an opportunistic human pathogen that secretes multiple extracellular virulence factors detectable on solid media. This study characterized protease, elastase, hemolysin, siderophore, and pyocyanin production of ten clinical isolates compared with the PAO1 reference strain using skim-milk agar, elastin Congo red agar, blood agar, CAS agar, and King’s A medium. Quantitative image analysis demonstrated significantly larger proteolytic halos in clinical isolates (21.4 ± 2.3 mm) than PAO1 (15.2 ± 1.8 mm; p = 0.003). Elastase activity increased by 38% under iron-limited conditions (p = 0.001). β-hemolysis zones were observed in 80% of isolates, with mean diameters of 18.7 ± 2.1 mm versus 12.5 ± 1.6 mm in controls (p = 0.005). Siderophore production showed a 1.6-fold increase during iron restriction (p < 0.001). Sub-inhibitory ciprofloxacin significantly reduced pyocyanin intensity by 42% (p = 0.004). These findings demonstrated statistically significant variability in secreted virulence phenotypes and highlighted environmental modulation of the P. aeruginosa plate-detectable secretome.